PENGARUH BOPO, NPL, CAR TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 - 2019 - Hidayati, Kanitha; Rispantyo, Rispantyo; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The role of banking is currently very important in the financial system. Agood financial system will have a positive effect on banking performance. Thisstudy aims to determine the effect of banking risk which is analyzed using the ratioof BOPO, NPL, CAR on financial performance in banking companies listed on theIndonesia Stock Exchange. The sampling method used was purposive samplingmethod. The number of samples is 15 companies. The data analysis method usedis multiple linear regression analysis. The results show that BOPO and NPL havea significant negative effect on financial performance while CAR has a significantpositive effect on financial performance.Keywords: Financial Performance, Operating Expenses to Operating Income,Non Performing Loans, Capital Adequacy Ratio